Democratic state and corporate business: The unfolding relationship in the era of economic liberalisation - Oberoi, Roopinder (2015)
The analysis of state-business relations and the process by which public policies are crafted is crucial for understanding the nature and trajectory of contemporary development approaches and their distributional and social consequences in democratic polity. Of particular concern is the question of business clout and its sway on public institutions and policy making. Worrisome, however, is that in the process of crafting the liaison with business, issues of institutional capture and the facilitation and legitimisation of corporate capitalism are often overlooked. Variety of methods, including corruption by business associations as well as influence exercised via less overt channels, result in the reciprocal dependence between business and government. This article particularly focuses on analysing the changing nature of engagement between business and state in Indian polity while applying historiography as a technique to spotlight on political economy of reforms. Topical studies are revisiting this liaison and have arrived at the conclusion that, no doubt, there has been an ascendancy in capitalist sway over the state of late, but these studies reaffirm that capitalist class was always key agent precisely from the beginning and has exercised unremitting pressure till day. - Reproduced.
Keywords: Economic liberalization; Business management